Factors affecting performance of the ethnic minority students in secondary schools - Kalam, Md. Abul (BRAC Research and Evaluation Division (RED), 2019)
BRAC started working with secondary education through its post primary basic education program since 2001. After piloting in 20 schools BRAC is now operating this program in 250 schools of which 175 have different proportions of ethnic minority students. This particular study attempted to explore the level of and factors affecting the performance of the ethnic minority students in secondary schools. Five schools having at least 25% ethnic minority students, one from five areas of Kalmakanda, Kulaura, Haluaghat, Panchbibi and Dhamoirhat were selected purposively for the study. Three methods/techniques of classroom observation, scanning of documents and group discussion with teachers, ethnic minority students and their parents, were followed for data collection using checklists. The study found that ethnic minority students were lagged behind their Bangalee classmates in their performances in terms of completion, noncompletion, dropout and repetition in different classes, attendance at school, and results in public and school examinations. Several factors were found which might affect ethnic minority students' performance in secondary schools. Prominent among these factors were attitude of teachers towards ethnic minority students' potentiality; poor economic condition; relationship with Bagalee classmates; treatment by teachers in the classroom; private tutor dependent education; lack of helping hand in study at home; lack of awareness among parents; attendance at school; lack of security; lack of educational environment at home, etc. The study also found that schools' responses to these factors was very few with limited or no results. Furthermore, the study gained some suggestions from different groups of respondents for improving the situation.